PENINGKATAN BRANDING & IDENTITAS ILMU KOMUNIKASI UNTIRTA MELALUI RANCANGAN VISUAL MERCHANDISE - Adhany, Allysa Farra; Rangga Gumelar (AKSA: Jurnal Desain Komunikasi Visual, 2024)
Merchandise design has evolved into more than just functional clothing, but also as an identity element and a tool to enhance product branding. The focus of this research is on the visual merchandise design process for Untirta Communication Sciences, a state campus in Banten. Through a visual approach and graphic design, this design is made attractive and in accordance with the brand character. It is important to create a balance between innovation, brand identity, creativity and understanding trends in the branding process. This research uses a design method with several stages. In this research, it is explained that typography, visual unity, and adaptation to the target audience are key aspects in every design, especially for merchandise.